2012
DOI: 10.1007/s13280-011-0245-2
|View full text |Cite
|
Sign up to set email alerts
|

Black Disease (Terpios hoshinota): A Probable Cause for the Rapid Coral Mortality at the Northern Reef of Yongxing Island in the South China Sea

Abstract: The northern reef of Yongxing Island, the largest reef island of the Xisha Islands in the South China Sea, was in good condition with significant cover of scleractinian corals until 2002. Surveys in 2008 and 2010, however, found that coral coverage had declined rapidly and severely, implying that catastrophic coral mortality occurred during the past 8 years. A blackish mat was observed covering live and dead corals in both 2008 and 2010 that was identified as an encrusting sponge, Terpios hoshinota, by special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 12 publications
3
30
0
Order By: Relevance
“…Polluted seawater following anthropogenic impacts favours the development of T.hoshinota as seen in Guam 2,6 and Green Island 16 . Our findings contradict these above statements and is more in line with the findings of Shi et al 8 , who observed T.hoshinota outbreak in unpolluted areas of Yongxing Island (South China Sea). Prevalence of T.hoshinota in the southeastern reefs of India (~800km from Lakshadweep) is due to high anthropogenic stress and its close proximity to mainland 10–12 , however, a similar conclusion cannot be applied in the case of Lakshadweep because of its isolated geography 17 and with comparatively less anthropogenic activities.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Polluted seawater following anthropogenic impacts favours the development of T.hoshinota as seen in Guam 2,6 and Green Island 16 . Our findings contradict these above statements and is more in line with the findings of Shi et al 8 , who observed T.hoshinota outbreak in unpolluted areas of Yongxing Island (South China Sea). Prevalence of T.hoshinota in the southeastern reefs of India (~800km from Lakshadweep) is due to high anthropogenic stress and its close proximity to mainland 10–12 , however, a similar conclusion cannot be applied in the case of Lakshadweep because of its isolated geography 17 and with comparatively less anthropogenic activities.…”
Section: Resultssupporting
confidence: 86%
“…Since its first occurrence, it has been observed in several coral reef localities around the globe viz. the Great Barrier Reef 3 , Papua New Guinea 4 , Taiwan 5 , Philippines 6 , Indonesia 7 , South China Sea 8,9 , Thailand 6 , Palk Bay (PB)/Gulf of Mannar (GOM) (India) 10–12 , Maldives 13 , Mauritius 14 and our present observation, confirms that the species has further extended its habitat into the pristine atolls of Lakshadweep (Figure 1) (Indian Ocean) and requires urgent attention.…”
Section: Introductionsupporting
confidence: 82%
“…This sponge has become a serious problem on some coral reefs of the Western Pacific, devastating large areas of flourishing coral communities (Plucer‐Rosario ; Shi et al . ; Wang et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The encrusting cyanobacteriosponge Terpios hoshinota may become another agent hindering coral recovery in some Maldivian reefs, such as those in Baa Atoll (T. Le Berre personal communication) where this sponge is spreading rapidly on sheltered reefs in the lagoon and killing different coral species and thus covering large patches of the reef. This sponge has become a serious problem on some coral reefs of the Western Pacific, devastating large areas of flourishing coral communities (Plucer-Rosario 1987;Shi et al 2012;Wang et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Like coral bleaching, in most cases, WS also causes the loss of all or some of the symbiotic algae and photosynthetic pigments in coral animals, with the white calcium carbonate skeleton becoming visible. In the South China Sea, many diseases, such as WS, white spot disease, coral black disease, yellow inflammatory-like syndrome, pink disease and brown band disease, occurred recently in some stony corals, and the coverage of live coral has declined by more than 30% over the past few decades [5-8]. However, despite the one ciliate documented to link to brown band disease, little information is available regarding the species identities of the microbial pathogens of coral diseases in this area.…”
Section: Introductionmentioning
confidence: 99%